Inhibition of Id proteins by a peptide aptamer induces cell-cycle arrest and apoptosis in ovarian cancer cells - Shenegelegn Mern, Demissew; Hasskarl, Jens; Burwinkel, Barbara (British journal of cancer, 2010)
Inhibitors of DNA-binding proteins (Id1-4), lacking the basic DNA-binding domain, function as dominant inhibitors of cell-cycle regulators. Overexpression of Id proteins promotes cancer cell proliferation and resistance against apoptosis. Level of Id protein expression, especially of Id1, correlates with poor differentiation, enhanced malignant potential and more aggressive clinical behaviour of ovarian tumours. Although overexpression of Ids has been found and shown to correlate with poor clinical outcome, their inhibition at protein level has never been studied.
Gesehen am 19.04.2023